Diarrhea in suckling lambs is associated with changes in gut microbiota, serum immunological and biochemical parameters in an intensive production system - Zhong, Tao; Wang, Yaxuan; Wang, Xinlu; Freitas-de-Melo, Aline; Li, Hua; Zhan, Siyuan; Wang, Linjie; Cao, Jiaxue; Dai, Dinghui; Guo, Jiazhong; Li, Li; Zhang, Hongping; et al. (Frontiers in Microbiology, 2022)
The incidence of diarrhea in lambs is frequent in large-scale sheep farms, which greatly impacts the growth and health of lambs. The aim of this study was to assess the changes in serum biochemical and immunological parameters and gut microbiome composition in suckling lambs suffering from diarrhea or not, reared on an intensive commercial farm. We found a reduced diversity of intestinal bacteria in suckling lambs suffering from diarrhea. Firmicutes and Bacteroides were the dominant flora of both diarrheic and healthy lambs, but the Bacteroides decreased in diarrheic lambs. Compared with healthy lambs, the proportion of aerobic bacteria, facultative anaerobic bacteria, and stress tolerant bacteria increased in lambs suffering form diarrhea, while that of anaerobic bacteria and potential pathogenic bacteria decreased slightly. In addition, the contents of total cholesterol, immunoglobulins (Ig) G, and IgM in the serum lambs suffering from diarrhea, were lower than those of healthy lambs. This study explored the association between intestinal microbial community structure and diarrhea in Hu lambs, and provided a theoretical reference point for the treatment of diarrhea in lambs.